From High Fidelity (1995) to Funny Girl (2014) or What Makes Nick Hornby’s Novels so Popular - Chifane, Cristina (Journal of History Culture and Art Research, 2015)
From High Fidelity (1995) to Funny Girl (2014) or What Makes Nick Hornby’s Novels so Popular Abstract The common and perhaps the most fascinating characteristic of all Nick Hornby’s novels is that they tackle contemporary problems of ordinary people. As a consequence, the readers will plunge into a world of failed relationships; fear of commitment; depression; lack of emotional stability; teenage anger and imbalance; frustration and obsession; invented maladies, sons or parties; disappointment and self-pity as well as useless single or group therapies. In spite of their dark problematic, Hornby’s novels have enjoyed popularity and continue to exert the sort of fascination that only brilliant literary pieces may produce. From such a point of view, this paper will try to solve the puzzle called Nick Hornby constructing and deconstructing the elements that make up his unique writing style.